2023
DOI: 10.1101/2023.03.22.533675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Enumeration of the Human Proteostasis Network. 2. Components of the Autophagy-Lysosome Pathway

Abstract: The condition of having a healthy, functional proteome is known as protein homeostasis, or proteostasis. Establishing and maintaining proteostasis is the province of the proteostasis network, approximately 2,700 components that regulate protein synthesis, folding, localization, and degradation. The proteostasis network is a fundamental entity in biology that is essential for cellular health and has direct relevance to many diseases of protein conformation. However, it is not well defined or annotated, which hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…Thus, we wanted to demonstrate that our gene sets similarly show selective UPR activation induced by ER proteostasis perturbations. We monitored the expression of stress pathway target genes in K562 cells CRISPRi-depleted of the 215 enumerated proteins comprising discrete ER proteostasis pathways including ER chaperones/folding enzymes, glycoproteostasis factors, protein degradation pathways, and protein targeting/trafficking pathways ( Proteostasis Consortium et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we wanted to demonstrate that our gene sets similarly show selective UPR activation induced by ER proteostasis perturbations. We monitored the expression of stress pathway target genes in K562 cells CRISPRi-depleted of the 215 enumerated proteins comprising discrete ER proteostasis pathways including ER chaperones/folding enzymes, glycoproteostasis factors, protein degradation pathways, and protein targeting/trafficking pathways ( Proteostasis Consortium et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we sought to probe the activation of these stress-responsive signaling pathways in K562 cells CRISPRi-depleted of individual mitochondrial proteostasis factors. The mitochondrial proteostasis network comprises 94 chaperones/folding enzymes, proteases, and import factors ( Proteostasis Consortium et al. , 2022 ), 82 of which were included in the published Perturb-seq dataset ( Replogle et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…127 To scrutinize whether the induced nuclear localization of TFEB by CCT020312 in HeLa cells is consistent with its transcriptional activation, we conducted RNA-Seq analysis of the same batch of cells treated with CCT020312 (2.5µM) for 20 h. RNA-Seq analysis revealed that CCT020312 treatment (2.5µM) significantly (adjusted p-value < 0.05) upregulated 1039 genes and downregulated 1177 genes (Supplemental Table 1), including 152 associated with the autophagy-lysosomal pathway (Figure 3C). 128 To discern which genes are specifically modulated by the TFEB transcriptional program, we cross-referenced our findings with TFEB transcriptional program gene sets from previous studies, 125127,129 identifying 172 genes significantly altered by CCT020312 treatment (Supplemental Table 1, Figures 3C, 3D, S3L). These genes, including lysosomal acid hydrolases and selective autophagy receptors exhibited significant upregulation relative to vehicle-treated samples, establishing a link between CCT020312-induced gene expression changes and autophagy-lysosomal pathway regulation (NEU1: 2.1x DMSO, CTSL: 1.5x DMSO, ASAH1: 1.4x DMSO, LIPA: 1.4x DMSO, CTSD: 1.3x DMSO, CTSF: 1.3x DMSO, SQSTM1: 1.6x DMSO, CALCOCO2: 1.4x DMSO).…”
Section: Resultsmentioning
confidence: 99%
“…Pathway enrichment was done with ClusterProfiler (v4.6.2) against the Gene Ontology 91 and KEGG 92 databases, and custom gene sets of functional pathways related to aging [93][94][95][96][97][98][99] . For each tissue, all genes that underwent differential expression analysis were used as the background gene set.…”
Section: Pathway Enrichment Analysismentioning
confidence: 99%